UNSUR SEMANTIK DEBAT PUBLIK PASANGAN CALON PADA PILGUB JATIM 2018: KAJIAN ANALISIS WACANA KRITIS [Semantic Elements of the Candidate Pair’s Public Debate in the 2018 East Java Governor Election A Study of Critical Discourse Analysis (CDA)] - Sueb Sueb (SAWERIGADING, 2022)
The title of this article is "Semantic Elements / Meaning of the Words of the Public Debate of Candidate Pairs in the 2018 East Java Gubernatorial Election in conveying the East Java development program for the Next Five Years: A Study of Critical Discourse Analysis (AWK)." The issue raised is how the semantic element/meaning of the word public debate of the candidate pairs in the 2018 East Java Pilgub in conveying the East Java development program for the next five years: Critical Discourse Analysis (AWK). The objectives of this study are: to describe, interpret, and explain the semantic elements/meaning of words used by the candidate pairs in the 2018 gubernatorial election in conveying the East Java development program for the next five years. The theories used are public debate, campaign language, pilkada, and critical discourse analysis/awk: public debate, campaign, ideology, election, and critical discourse analysis/AWK. The research method used is the qualitative method. The results showed that the semantic elements/meaning of words (1) experience value: (a) ideologically fought words, (b) presented metaphors, (2) relational values: (a) euphemistic expressions, (b) choice of words formal, and (3) expressive value: (a) words that express positive evaluations, (b) words that express negative evaluations.